2016
DOI: 10.1111/1365-2478.12403
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic pressure sensitivity anisotropy of a calcareous shale

Abstract: Optimizing the productivity of nonconventional, low‐permeability “shale” reservoirs requires detailed knowledge of the mechanical properties of such materials. These rocks' elastic anisotropy is acknowledged but usually ignored due to difficulties in obtaining such information. Here we study in detail the dynamic and static elastic properties of a suite of calcareous mudstones from the nonconventional Duvernay reservoir of Alberta, Canada. The complete set of transversely isotropic elastic constants is obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 85 publications
(137 reference statements)
1
31
0
Order By: Relevance
“…Further insights could be gained from the spatiotemporal variations in these two components (Figure c). It has been reported that the amount of anisotropy caused by HF in the Duvernay shale can reach up to 30% in rock physical experiments (Ong et al, ). The thickness of the total shale formation is over 90 m (Davis & Karlen, ) and, due to the nearly parallel emergence angle, the range of anisotropy within the HF area is estimated to be 200–400 m, which accounts for 5–10% of the lengths of ray paths.…”
Section: Discussionmentioning
confidence: 99%
“…Further insights could be gained from the spatiotemporal variations in these two components (Figure c). It has been reported that the amount of anisotropy caused by HF in the Duvernay shale can reach up to 30% in rock physical experiments (Ong et al, ). The thickness of the total shale formation is over 90 m (Davis & Karlen, ) and, due to the nearly parallel emergence angle, the range of anisotropy within the HF area is estimated to be 200–400 m, which accounts for 5–10% of the lengths of ray paths.…”
Section: Discussionmentioning
confidence: 99%
“…The derived effective stress coefficient for ultrasonic velocities (dynamic) in the same specimens [ Ma and Zoback , ] was found to differ from that by the static volumetric strain shown in this study. Recent studies on dynamic and static properties in the same shale specimens also confirmed the fundamental differences between the two physical quantities and their sensitivities to stresses [ Meléndez‐Martínez and Schmitt , ; Ong et al , ]. Although the transmitting waves through the rock also induce strain (by vibration), the amount of dynamic deformation is a few orders smaller than the strain produced by the static loading [cf.…”
Section: Discussionmentioning
confidence: 99%
“… G 13 denoted by the shear modulus along the perpendicular direction of the isotropic plane is assumed to 1.7 GPa [cf. Amadei , ; Debasis and Kumar , ; Ong et al ., ]. The material parameters for stiff (isotropic) and soft (transverse isotropic) layers are summarized in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Notation: the rotational axis of symmetry is parallel to the x 3 axis, and x 1 x 2 coordinate system planes are identical [cf. Ong et al ., ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation